2020
DOI: 10.12697/eha.2020.8.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Kaasava hariduse tähendus ja tõhusa rakendamise tegurid Eesti kontekstis: õpetajaid koolitavate või nõustavate spetsialistide vaade

Abstract: Kaasava hariduse teemalise õpetajakoolituse arendamine on aktuaalne nii Eestis kui ka rahvusvaheliselt. Õpetajate oskuste ja teadmiste kujundamisel on otsustav roll spetsialistidel, kes õpetajaid koolitavad või nõustavad. Seejuures on tähtis, et spetsialistid omaksid ühist arusaama kaasava hariduse tähendusest ning tõhusatest rakendamise viisidest. Siinse uuringu eesmärk oli välja selgitada, kuidas mõistavad õpetajaid koolitavad või nõustavad spetsialistid kaasava hariduse tähendust ja milliseid tegureid nad p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 20 publications
0
10
0
18
Order By: Relevance
“…As shown by recent TALIS survey, this is an area of concern and needs further professional development in many TALIS countries (OECD 2020). Moreover, some countries, including Eastern Europe and former Soviet countries are experiencing bigger challenges (Kivirand et al 2020;Stepaniuk 2018). Due to the past histories of educational systems and teacher education programmes in many of these countries, teacher preparation has not paid sufficient attention to how to teach students with special educational needs together with their peers in an inclusive setting.…”
Section: Discussionmentioning
confidence: 99%
“…As shown by recent TALIS survey, this is an area of concern and needs further professional development in many TALIS countries (OECD 2020). Moreover, some countries, including Eastern Europe and former Soviet countries are experiencing bigger challenges (Kivirand et al 2020;Stepaniuk 2018). Due to the past histories of educational systems and teacher education programmes in many of these countries, teacher preparation has not paid sufficient attention to how to teach students with special educational needs together with their peers in an inclusive setting.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the implementation of inclusive education is supported by a shared understanding of inclusive education (Florian, 2017). The results of previous research conducted in Estonia have shown that the meaning of inclusive education is interpreted differently among specialists, teachers and education managers (Häidkind & Oras, 2016;Kivirand et al 2020).…”
Section: A Model Of Inclusive Education In the Context Of Estonian Prmentioning
confidence: 98%
“…Jagatud arusaam kaasavast haridusest mõjutab selle rakendamist (Florian, 2017;Stone, 2014;Sukumaran et al, 2015). Varasemate Eestis tehtud uuringute tulemused on näidanud, et kaasava hariduse tähendust tõlgendatakse spetsialistide, õpetajate ja haridusjuhtide seas erinevalt (Häidkind & Oras, 2016;Kivirand et al, 2020).…”
Section: Arutelu Ja Järeldusedunclassified
See 2 more Smart Citations